A new model of the formation of Pennsylvanian iron carbonate concretions hosting exceptional soft‐bodied fossils in Mazon Creek, Illinois. Issue 6 (15th July 2016) - Cotroneo, S.; Schiffbauer, J. D.; McCoy, V. E.; Wortmann, U. G.; Darroch, S. A. F.; Peng, Y.; Laflamme, M.
Abstract: Preservation of Pennsylvanian‐aged (307 Ma) soft‐bodied fossils from Mazon Creek, Illinois, USA, is attributed to the formation of siderite concretions, which encapsulate the remains of terrestrial, freshwater, and marine flora and fauna. The narrow range of positive δ 34 S values from pyrite in individual concretions suggests microenvironmentally limited ambient sulfate, which may have been rapidly exhausted by sulfate‐reducing bacteria. Tissue of the decaying carcass was rapidly encased by early diagenetic pyrite and siderite produced within the sulfate reduction and methanogenic zones of the sediment, with continuation of the latter resulting in concretion cementation. Cross‐sectional isotopic analyses (δ 13 C and δ 18 O) and mineralogical characterization of the concretions point to initiation of preservation in high porosity proto‐concretions during the early phases of microbially induced decay. The proto‐concretion was cemented prior to compaction of the sediments by siderite as a result of methanogenic production of 13 C‐rich bicarbonate—which varies both between Essex and Braidwood concretions and between fossiliferous and unfossiliferous concretions. This work provides the first detailed geochemical study of the Mazon Creek siderite concretions and identifies the range of conditions allowing for exceptional soft‐tissue fossil formation as seen at Mazon Creek.